USING OF LKPD BASED ON LOCAL EXCELLENCES OF SOUTH SUMATERA TO IMPROVE THE STUDENT ACTIVITIES AND LEARNING OUTCOMES - Suratmi Suratmi; Laihat Laihat; Rizki Fitrianti (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
Abstract. The purpose of this study was to improve the learning outcomes and activites of class V subtheme Komponen Ekosistem using LKPD based local excellence in south Sumatra SD Negeri 163 Palembang. This study uses the method of classroom action research in two cycles of action. The techniques of data collection are test and observation. This classroom action research has 4 stages that must be fulfilled, namely planning, implementation, observation and reflection. The research subjects in this study were students of VB class SD Negeri 163 Palembang with a total of number 32 students consisting of 17 males and 15 females. The results showed that the value of student learning outcomes has increased, this can be seen in the percentage of students' learning completeness in the first cycle of 56.25% with an average value of 67.8, in the second cycle the percentage of student learning completeness increased to reach 84,37% with an average value of 82.6. The results of observations, the activity of students have increased, in the first cycle the percentage of activity of students in learning reached 73.43% with the active category, in the second cycle increased to 83.59% in the very active category. So, it can be concluded that using a LKPD based local excellence in south Sumatra can improve the learning outcomes and activities of class V students in SD Negeri 163 Palembang. Keywords: LKPD, local excellence, Learning Outcomes, students activity